Rising atmospheric carbon dioxide concentrations increase gaps of rice yields between low- and middle-to-high-income countries - Song, Lian; Tao, Ye; van Groenigen, Kees Jan; Chang, Scott X.; Peñuelas, Josep; Zhang, Jishuang; You, Liangzhi; Cai, Chuang; Wang, Songhan; Jiang, Yu; Ma, Chuanqi; Yan, Xiaoyuan; et al. (Springer, 2024)
The rising carbon dioxide concentrations are expected to increase future rice yields. However, variations in the CO2 fertilization effect (CFE) between rice subspecies and the influence of concurrent global warming introduce uncertainty in future global rice yield projections. Here we conducted a meta-analysis of rising carbon dioxide field experiments and employed crop modelling to assess future global rice yields for the top 14 rice producing countries. We found a robust parabolic relationship between rice CFE and temperature, with significant variations between rice subspecies. Our projections indicate that global rice production in the 2050s is expected to increase by 50.32 million tonnes (7.6%) due to CFE compared with historical production. Because low-income countries will experience higher temperatures, the gaps (difference of Δyield) between middle-to-high-income and low-income countries are projected to widen from the 2030s to the 2090s under elevated carbon dioxide. These findings underscore the critical role of CFE and emphasize the necessity to increase investments in research and technology for rice producing systems in low-income countries.